Alimony in Islamic Family Law in Indonesia: Definition, Legal Basis, and Obligations Toward Former Wives and Parents - Ahmad Ikhsan Ramadhan; Nadya Arafah Zahra; Ghulam Ahmad Suryanegara; Humaeroh Humaeroh (Journal of Human Interaction and Social Studies, 2026)
Alimony constitutes a fundamental institution in Islamic family law that regulates financial responsibilities among family members and promotes welfare, justice, and social protection. This article examines the definition of alimony, its legal foundations, and the obligations arising toward former wives and parents within the framework of Indonesian Islamic family law. Employing a normative juridical approach and library-based research, the study analyzes primary legal sources, including the Qur’an, Hadith, and the Compilation of Islamic Law, alongside relevant scholarly literature and legal regulations. The findings reveal that alimony is not limited to material support but also embodies moral and social responsibilities rooted in Islamic legal principles. Its legal force extends beyond the marital relationship, encompassing post-divorce obligations through iddah maintenance and mut’ah, as well as the duty of financially capable children to support dependent parents. These obligations reflect the broader objectives of Islamic family law in safeguarding dignity, ensuring family welfare, and strengthening social justice through legally recognized mechanisms of support and protection.